Precision and Accuracy in Elemental Determination in Environmental Samples Using Instrumental Neutron Activation Analysis (Biological Sciences - PJSIR, 2005)
Thirty elements were determined in different environmental certified reference materials (CRMs) with high accuracy and precision using instrumental neutron activation analysis (INAA). The relative error of most of the elements was found to be within 10% and the standard deviation was less than 15%. The Z-score, as an analytical performance indicator, was also less than ±2. The accourate determination of various trace and major elements, at extremely low concentrations, usually present in very small amounts of airborne particulate matter on filter media was performed satisfactorily by INAA, which is otherwise regarded as a problem in such determinations. On the other hand, nevertheless, INAA appeared to be an inadequate method for the analysis of Ca because of the low count rate.